Challenges and Strategies in Early Teaching Experience: Voice of Novice EFL Indonesian Lecturers - Fairuz Putri Khalisa; Soni Mirizon; Eryansyah Eryansyah (VELES Voices of English Language Education Society, 2022)
For novice EFL lecturers, the early years of teaching are quite challenging, as what they find ‘ideal’ in pre-service education is different from the realities of the classroom. The unfamiliar curriculum, limited supports from institutions, and socialization issues are general challenges for new lecturers. This study aimed to explore the voices of novice EFL Indonesian lecturers about the challenges faced and the strategies used in their early teaching experience. In this qualitative case study, the data were collected through interviews with four participants (novice EFL Indonesian lecturers). This study found that there were two major challenges that novice EFL lecturers faced in their early teaching experience, namely student-related challenges (students’ low proficiency in English, students’ negative learning attitude, students’ low critical thinking) and institution-related challenges (unavailability of suitable syllabus and high demand of the university to the teachers). In responding to student-related challenges, novice EFL lecturers employed some strategies such as grouping students into mixed-ability groups, adjusting the materials to the student’s level of proficiency, setting rules and consequences with students, and designing activities that promote critical thinking. In coping with institution-related challenges, these teachers collaborate with other English lecturers to develop a module and they consult with their coordinators to navigate the situation.